Theology and religious studies in higher education: global perspectives - Bird, Darlene; Smith, Simon G. (Continuum advances in religious studies, 2009)
Theology and religious studies co-exist in the majority of departments in higher education institutions within the UK, yet there has been very little debate or discussion on how these two disciplines relate to one another in this context and on a more general level. This new collection of essays aims to redress the balance and to add to fruitful discussion in this area Including essays by some of today's leading academics on the sometimes contentious relationship between religious studies - or the study of religions - and theology, this volume is international in scope, with contributions from